Prioritizing water and nexus thinking at COP16 - CGIAR Initiative on NEXUS Gains (CGIAR, 2024)
Throughout the Convention on Biological Diversity COP16, NEXUS Gains played an active role in highlighting the importance of water–energy–food–ecosystems (WEFE) nexus approaches for improving sustainable water resources management and food systems, protecting biodiversity, and ensuring equitable access to clean energy.